P51 Unusual early clinical manifestation of bland – white – garland syndrome in a neonate. (June 2019) - Bakoš, Matija; Bartoniček, Dorotea; Dilber, Daniel; Malčić, Ivan; Šarić, Dalibor
Abstract : This case report describes a 24–day-old neonate who was admitted at our hospital because of tachypnoea, tachycardia, failure to thrive, and breastfeeding fatigue. He was a late preterm newborn; born at 36 th week of gestation with normal Apgar score. He manifested increased effort of breathing few hours after birth, while initially being treated for respiratory distress syndrome via High-Flow-Nasal-Cannula (HFNC) with 40% of inspired oxygen supplementation for 10 days. Because of persistent tachydispnoea and feeding difficulties in maternity, hospital antimicrobial treatment was initiated unsuccessfully. Afterwards, he has been misdiagnosed with a coronary fistula and sent to our hospital. Systolic murmur was noticed. ECG showed typical changes for the left heart ischemia – anteroseptal ischemia with negative T-vawe V1-V2, aVL and DII-DIII. There were no signs of cardiogenic shock. Our ECHO revealed moderately dilated left ventricle with slightly depressed systolic function, increased echogenicity of the papillary muscles, and mild mitral regurgitation. The dilatation of right coronary artery was also shown, but the left coronary artery was not visible. The diagnosis of Bland-White-Garland syndrome was set. The day after, he underwent cardiac catheterization when the diagnosis of anomalous origin of the left coronary artery from the pulmonary artery (ALCAPA syndrome) was confirmed. Few days later, Takeuchi procedure was performed as the method of repair. There were no major complications postoperatively. In the follow-up period he progressed favorably and now he is asymptomatic, but still has abnormal ECG. ECHO has shown significant supravalvular pulmonary stenosis. Discussion: ALCAPA is usually presented with signs of myocardial ischemia and dilated cardiomyopathy between the ages of two months throughout the adult period. The management of respiratory distress in the preterm newborn infant with oxygen supplementation had detrimental effect on myocardial perfusion and caused decrease in PVR with early presentation of DCM. This case emphasizes the importance of identifying the coronary origins as a routine part of a complete pediatric echocardiogram.